Corporate Criminal Liability for the Crime of Forgery of Export Documents According to Law of the Republic of Indonesia Number 17 of 2006 concerning Customs - T. Riza Zarzani; Ismaidar Ismaidar; Sukardi Sukardi (International Journal of Law, Crime and Justice, 2024)
Customs is everything related to the supervision of the traffic of goods entering or leaving the customs area as well as the collection of import and export duties. Based on this definition of customs, the Directorate General of Customs and Excise (DJBC) has a very strategic role in both supervision and service. Economic life between one country and another is increasingly interdependent so that legal provisions in the field of international trade and transnational business are increasingly necessary. As time goes by, the presence of corporations in the economy is like a double-edged sword. On the one hand, it can provide benefits for economic growth through state income in the form of taxes thereby increasing the country's foreign exchange and on the other hand, it can threaten state income because corporations often commit crimes to gain as much profit as possible by falsifying goods export documents. The 1945 Constitution of the Republic of Indonesia Article 1 paragraph 3 states that Indonesia is a legal state. In accordance with the concept of a rule of law, everything related to processes carrying out aspects of government power is based on law, including the law enforcement process in cases in the customs sector, especially in the export sector. This research uses normative legal research methods. Normative research is research carried out by examining library materials using data sourced from secondary data, namely primary legal materials, secondary legal materials and tertiary legal materials. Data collection in this research was carried out by document study and literature study. Then it is described qualitatively to make it easier to draw conclusions from the data. The aim of this research is to determine the factors that cause corporations to commit criminal acts of falsifying export documents and to find out what corporate criminal liability is for criminal acts of falsifying export documents according to Law of the Republic of Indonesia Number 17 of 2006 concerning Customs.